Methanol Production ‐ A Technical History. Issue 3 (1st July 2017) - Sheldon, Daniel
Global methanol production in 2016 was around 85 million metric tonnes (1), enough to fill an Olympic-sized swimming pool every twelve minutes. And if all the global production capacity were in full use, it would only take eight minutes. The vast majority of the produced methanol undergoes at least one further chemical transformation, more likely two or three before being turned into a final product. Methanol is one of the first building blocks in a wide variety of synthetic materials that make up many modern products and is also used as a fuel and a fuel additive. This paper looks at the last 100 years or so of the industrial history of methanol production.